THE USE OF INTERNET IN LANGUAGE TEACHING AND LEARNING ENGLISH AS A FOREIGN LANGUAGE - Kamal, Sirajudin (LET: Linguistics, Literature and English Teaching Journal, 2012)
Nowadays, we live in age of technology and unlimited communication whereas there are growing demands on everyone, including teachers and students, to be technologically literate. In this era, it is clear that English has been a global language, not only in general life but also in international education for specific. In education, the implementation of internet as the backbone of online-learning, online-course and dedicated course material servers, are not a new things. Moreover, internet as an   international computer network has very significant numbers of learning resources.